A methodology for predicting hybrid solar panel performance in different operating modes. (January 2019) - Fine, Jamie P.; Dworkin, Seth B.; Friedman, Jacob
Abstract: When a hybrid solar panel produces thermal energy, it can operate in either hybrid mode, or thermal-only mode. In hybrid mode, the panel produces both electrical power and thermal power, and in thermal-only mode, only thermal power is produced. It has been shown that the thermal performance of a hybrid panel can vary by 15% on average between these two modes, but panel manufacturers are only required to publish performance data for one mode. Other studies in the literature have found a difference in panel thermal performance between these two modes, but they do not discuss a methodology to estimate alternate mode performance using manufacturer-supplied data. To alleviate this gap in the literature, this study presents a novel methodology to estimate alternate mode thermal performance of a hybrid solar panel only using manufacturer-supplied data. To match the panel information that is typically available, the second-order thermal efficiency model is used to estimate thermal performance, and temperature dependent electrical characteristics are used to estimate electrical performance. Indoor testing using a solar simulator was carried out, and the detailed test results are included. Results show that using the proposed modification technique can estimate thermal performance within 4% of actual values on average. Highlights: Hybrid solar panel thermal efficiency depends on electrical operating mode. A method for predicting alternate mode performance is presented. Experimental data from liquid-based hybrid solar panel testing is included. Validation of the method using experimental test data is successfully carried out. The method predicts alternate mode thermal efficiency within 4% of measurements.